1) Solve ​2x2−5x−3=0and enter solutions below.

2) Push the "Graph It" Button to see a graph of `y=2x^{2}-5x-3`

1 answer

To solve the equation 2x^2 - 5x - 3 = 0, we can use the quadratic formula:

x = (-(-5) ± √((-5)^2 - 4*2*(-3))) / 2*2
x = (5 ± √(25 + 24)) / 4
x = (5 ± √49) / 4
x = (5 ± 7) / 4

The solutions are:
x = (5 + 7) / 4 = 3
x = (5 - 7) / 4 = -0.5

Therefore, the solutions to the equation are x = 3 and x = -0.5.

Please check the graph of y=2x^2-5x-3 by clicking the "Graph It" button.